Helicobacter Pylori Infection and Kidney Damage: Is There An Association? - Oruç, Meric; Köroğlu, Emine (Cerrahpaşa Medical Journal, 2022)
Objective: We aimed to investigate the association of Helicobacter pylori (H. pylori) infection with albuminuria in our study. Methods: A total of 1398 adults who were admitted to nephrology outpatient clinics between June 2020 and August 2020 consecutively were screened. Patients who underwent upper endoscopy in our hospital within 5 years before the date of admission to nephrology outpatient clinics and who had concurrent results of serum creatinine and spot urine albumin/creatinine ratio up to 3 months before upper endoscopy were included. Patients who were shown to have any unstable condition, active infectious disease, malignancy, immunosuppressive treatments, renal transplantation, glomerulonephritis, dialysis, acute kidney injury, and liver disease were excluded. Data regarding demographic, laboratory variables [complete blood count, fasting blood glucose, urea, serum creatinine. albumin, uric acid, lipids, glycated hemoglobin, C-reactive protein, and albumin/creatinine ratio], and endoscopic/histopathologic findings were collected from electronic medical records of the patients. Results: Ninety-six patients (42.7%, male) with a median age of 61 (interquartile range, 49.5-68) years were included in the study. Seventy-seven patients (80.2%) were diagnosed with chronic kidney disease. The prevalence of H. pylori infection rate in chronic kidney disease and non-chronic kidney disease patients was 39% and 42%, respectively (P = .802). The abnormal urine albumin/creatinine ratio was present in 65 patients (67.7%), including 63.2% (24/38) in H. pylori-infected patients and 70.7% (41/58) in H. pylori-uninfected patients (P = .440). There were no significant differences including patient demographics and clinical and laboratory variables between H. pylori (+) and H. pylori (−) patients. There were significant positive correlations between albuminuria and hypertension, fasting blood glucose, and glycated hemoglobin (r = 0.211, P = .040; r = 0.318, P = .002; r = 0.222, P = .040, respectively). A nearly significant positive correlation was found between albuminuria and the presence of moderate or severe H. pylori colonization (r = 0.189, P = .065). In the subsequent multivariate logistic regression model, no independent associations were found. Conclusion: These results show that there is no significant relationship between H. pylori infection and chronic kidney disease and/or albuminuria, but there may be an association between albuminuria and the presence of moderate or severe H. pylori colonization. Cite this article as: Oruç M, Köroğlu E. Helicobacter pylori infection and kidney damage: Is there an association? Cerrahpaşa Med J. 2022;46(1):50-55.